Body mass index and age of menarche in young girls - Dina Olivia; Melda Deliana; Supriatmo Supriatmo; Hakimi Hakimi; Siska Mayasari Lubis (Indonesian Pediatric Society, 2012)
Background Currently the age at onset of menarche is earlierthan in the past. Nutritional status has an important role inthe onset of menarche. Past studies have shOan associationbetween body mass index (BMI) in young girls and earlier onsetof menarche.Objective To assess an association between BMI and age at onsetof menarche.Methods This crossô€ˆsectional study was conducted in younggirls aged 10 to 15 years from Immanuel Elementary and JuniorHigh School, Medan in June 2010. We used purposive samplingto recruit subjects. After subjects underwent height and weightmeasurements, we calculated their BMIs. The association betweenBMI and initial age of menarche was assessed by Chi square test(P<O.05 v.ith a 95% confidence interval).Results Eightyô€ˆfive subjects participated in this study. There were44 subjects in the 5thô€€Š85th percentile ofBMI (nonnoweight), 19subjects with 85thô€€Š95th percentile of BMI (overweight) and 12subjects in the> 95th percentile ofBMI (obese). All obese subjectshad an earlier onset of menarche at ages 1Oô€ˆ 11 years, comparedto that of nonô€ˆobese subjects (P=O.OOOl).Conclusion Young girls v.ith BMI > 95th percentile had anearlier age at onset of menarche than young girls v.ith lower BMls.[Paediatr lndanes. 2012,52:309-12].